Two Cases of Probable Neuro-Behçet's Disease with Longitudinally Extensive Transverse Myelitis - Fujiwara, Shunya (Case Rep Neurol, 2021)
We report 2 cases of probable neuro-Behçet's disease (NBD) with longitudinally extensive transverse myelitis (LETM). In both cases, the patients presented paraplegia, as well as sensory, bladder, and rectal disturbances. Magnetic resonance imaging (MRI) of patient 1 showed continuous high signal intensity extending from the midbrain to the entire spinal cord in the central part of the cord on T2-weighted imaging (T2WI). Spinal MRI of patient 2 revealed high signal intensity extending from Th2 to Th10 in the central part of the cord on T2WI. Both patients received high-dose methylprednisolone. A continuous lesion from the midbrain to the entire spinal cord as in patient 1 has not been previously reported. Patient 2 dramatically improved by infliximab therapy. The present cases suggest that NBD should be considered as a differential diagnosis in patients with LETM.